Autologous Stem Cells Combined Core Decompression for Treatment of Avascular Necrosis of the Femoral Head: A Systematic Meta-Analysis. (3rd August 2017) - Xu, Shibing; Zhang, Lei; Jin, Hongting; Shan, Letian; Zhou, Li; Xiao, Luwei; Tong, Peijian
Abstract : Objective . This study aims to systematically evaluate the efficacy and safety of core decompression combined transplantation of autologous bone marrow stem cells (CDBMSCs) for treatment of avascular necrosis of the femoral head (ANFH). Methods . Randomized controlled trials (RCTs) regarding effectiveness of core decompression combined transplantation of autologous bone marrow stem cells for treating ANFH were searched in 8 comprehensive databases prior to September 2016. The data analysis was performed by using the RevMan version 5.3. Results . A total of 11 studies with 507 participants were included. Results showed that CDBMSCs group was more effective than CD group in increasing Harris hip score, decreasing necrotic area of femoral head, collapse of femoral head, and conversion to total hip replacement incidence. In the subgroup analysis, the results did not change in different intervention measure substantially. In addition, the safety of CDBMSCs for ANFH is reliable. Conclusion . Based on the systematic review, our findings suggest that core decompression combined transplantation of autologous bone marrow stem cells appeared to be more efficacious in the treatment at early stages of ANFH.